Mental Health Researchers' Views About Service User Research: A Literature Review. (2nd December 2018) - Happell, Brenda; Gordon, Sarah; Bocking, Julia; Ellis, Pete; Roper, Cath; Liggins, Jackie; Platania-Phung, Chris; Scholz, Brett
Abstract: Services users are becoming actively involved in mental health research. How this is perceived by other researchers is not well known. The aim of this article is to review the international literature exploring other mental health researchers' views of service users conducting research, between 1996 and 2016. Searches of multiple databases (PubMed, PsycINFO, CINAHL, and Google Scholar) were undertaken. Combinations of terms related to service user research and mental health researcher perspectives, views, and attitudes were used. Manual inquiry of reference lists was also undertaken. Relevant papers were coded by topic, location, study design, and other dimensions. Five articles met inclusion criteria. Most referred to perceived benefits, such as greater validity of research findings, challenges of collaborating with service users, and the validity of research findings. There was some evidence of more openness to mental health service users providing suggestions, preferably in early stages of the research process. Reluctance to co-research with service users was reported. There is limited research directly addressing other mental health researchers' views about service user research; barriers to inclusion (whether involvement, co-production or user-controlled) and creating incongruence with health policy statements. Further research to more fully understand these attitudes and how they might be influenced is warranted.